Original articleEvaluation of lymphocyte subsets and cytokine concentration in patients with schizophrenia - Wójciak, Paweł; Remlinger-Molenda, Agnieszka; Sobieska, Małgorzata; Kostrzewa, Artur; Rybakowski, Janusz (Neuropsychiatria i Neuropsychologia/Neuropsychiatry and Neuropsychology, 2012)
Introduction : Schizophrenia is associated with immune system dysfunction. These dysfunctions are reflected, among others, in changes of lymphocyte subsets and cytokine levels. Aim of the study: To evaluate lymphocyte subsets and cytokine concentration in patients with schizophrenia. Material and methods: Lymphocyte subsets evaluation (CD3+, CD4+, CD8+, CD16+, CD19+, CD4/CD8) was performed in 28 patients with schizophrenia (12 men and 16 women aged from 19 to 56 years) using the flow cytometry method. The cytokine evaluation (sIL-2R, IL-4, IL-6) was performed in 32 patients with schizophrenia (15 men and 17 women aged from 29 to 56 years) using the ELISA method. The evaluation was also performed in 32 healthy control subjects (16 men and 16 women aged from 23 to 61 years). Results: Statistically significant differences were observed in lymphocyte subsets between schizophrenia patients and healthy control subjects (increase of CD19+, CD4/CD8 during exacerbation and increase of CD4/CD8 in remission). There were no significant differences between schizophrenic men and women in the above parameters during exacerbation and remission of schizophrenia. Statistically significant differences were observed in cytokine concentration between patients during acute episodes of schizophrenia and healthy control subjects (higher sIL-2R level), but not in remission. Also, there were significant differences between patients in exacerbation of schizophrenia and remission (higher IL-4 level). Conclusions: The results obtained confirm changes of immune system activity in schizophrenia including both activation and suppression at the same time. This may suggest an immunological imbalance during schizophrenia.